Simultaneous determination of 14 analgesics in postoperative analgesic solution by HPLC–DAD and LC–MS/MS - Manman Yao; Baoxia Fang; Jinguo Yang; Sicen Wang; Fuchao Chen (BMC Chemistry, 2024)
Abstract A green, efficient, sensitive and accurate detection method by HPLC–DAD and LC–MS/MS was developed and validated for the quantification of morphine, hydromorphone, oxycodone, ketamine tramadol, dezocine, ropivacaine, remifentanil, butorphanol, bupivacaine, droperidol, fentanyl, lornoxicam and sufentanil. The 14 mixtures were chromatographed via HPLC–DAD method which employed 0.05 mol/L potassium dihydrogen phosphate solution-acetonitrile as the mobile phase, the analytes were gradient elution on a SinoChrom ODS-BP C18 column with a total separation time of 35 min, and 14 mixtures showed a good linear relationship in the linear range. The Limit of Quantitation (LOQ) ranged from 0.10 to 20.0 µg/mL, the inter-day and intra-day precision of each analyte is within 1.1–2.0% and 0.4–1.3%, and the average absolute recovery of all compounds was above 98%. The LC–MS/MS method was used to successfully separate the 14 mixtures within 10 min which employed 0.1% formic acid-acetonitrile as the mobile phase, the analytes were gradient elution on a ACQUITY UPLC-BEH C18 column with a total separation time of 13 min, and 14 mixtures showed a good linear relationship in the linear range. The LOQ ranged from 0.005 to 0.2 ng/mL, the inter-day and intra-day precision of each analyte is within 1.2–4.1% and 0.6–3.3%, and the average absolute recovery of all compounds was above 93%. The proposed method has been successfully applied in the clinic and provides a strong technical basis for the quantitative detection of these 14 mixtures for detecting drug abuse, and for studying the stability and compatibility of analgesic solutions. The proposed methods were validated against ICH guidelines.